Preparing a rat brain tissue samples for acetylcholinesterase activity measurement - the MM method - Marinković, Sonja; Đukanović, Đorđe; Mandić-Kovačević, Nebojša; Uletilović, Snežana; Cvjetković, Tanja; Maksimović, Žana M (Scripta Medica, 2021)
Background/Aim: Organophosphorus compounds (OP) bind to acetylcholinesterase (AChE) causing an irreversible inhibition of the enzyme. When doing in vivo studies of OP intoxication, to precisely measure AChE activity in the brain tissue it is necessary to remove as much blood from the brain as possible. By doing so, interference of the OPs present in the blood is avoided. Usually this demands expensive equipment, therefore, the aim of this study was to find a simple and economical method to eliminate the blood from brain blood vessels. Methods: Wistar albino rats were divided into four groups named Control (C), Control washout (CW), Paraoxon (Pox) and Paraoxon washout (PoxW) group. Rats in Pox and PoxW were treated with 0.25 mg/kg paraoxon subcutaneously (sc), while C and CW received 1 mL/kg sc saline instead. The “Marinković-Maksimović” (“MM”) method was performed in rats from PoxW and CW groups. Activity of AChE was measured both in erythrocyte lysate and in brain tissue using spectrophotometry. Results: Macroscopic examination revealed that the elimination of blood was achieved in CW and PoxW groups. Activity of AChE in homogenised brain tissue was expectedly lower in the Pox and PoxW group, when compared to C and CW group, respectively. The CW group had a lower value of AChE activity in the brain tissue compared to C group, while activity of AChE in the PoxW group was statistically higher than in the Pox group (p = 0.044). Conclusion: The MM method provides good elimination of blood from the brain. Together with blood, present confounding factors that interfere with analysis in homogenised brain tissue, were also eliminated.